Random or referral hiring: When social connections matter - Catia Nicodemo; Rosella Nicolini (Institute for the Study of Labor (IZA), 2012)
This study investigates the existence of hiring criteria associated with the degree of social connections between skill and low-skill workers. We provide evidence about to what extent managers rely on their social connections in recruiting low-skill workers rather than on random matching. As one unique feature we follow an approach for a posted wage setting that reflects the main features of the Spanish labor market. By working with sub-samples of high and low-skill workers we are able to assess that the recruitment of low-skill immigrants quite often follows a referral strategy and we identify interesting irregularities across the ethnic groups. As a common feature, referral hiring is usually influences by the ethnicity of the manager and the relative proportion of immigrants within the firm. Under these perspectives, our study outlines new insights to evaluate the future perspectives of the Spanish labor market.
urn:nbn:de:101:1-201204239872
Keywords: J15; J21; J24; J61; J71; 330; ethnicity; hiring strategies; social networks; Arbeitsnachfrage; Ungelernte Arbeitskräfte; Personalbeschaffung; Ethnische Gruppe; Soziales Netzwerk; Spanien